Design and Simulation of a Novel Planetary Gear Mixer for Dry Particle Materials - Zhang, Lei; Bao, Jiusheng; Zhang, Qingjin; Yin, Yan; Liu, Tonggang; Huang, Shan (Recent Patents on Mechanical Engineering, 2020)
Background: Mixer with excellent performance is the essential premise for high-quality mixture production to ensure uniformity. In the fields of food, pharmacy, powder metallurgy and machinery industry, materials mixing is an indispensable process. At present, the mixing efficiency and performance of the traditional mixer are very low, which has its own limitations, and it is difficult to ensure the quality of the mixture, which seriously affects the safety and reliability of the mixture products such as synthetic drugs, chemical reagents, cement, synthetic fiber, etc. Objective: In order to improve the mixing performance by improving the mixing uniformity, volume utilization, reducing the mixing time and mixing blind area, a novel planetary gear mixer for dry particle materials is designed. Its blades can rotate and the angle of attack can be changed at any time, which realizes the multi-degree of freedom movement of the blades. Methods: Firstly, the shortcomings of three kinds of traditional mixers are compared and analyzed; a novel planetary gear mixer for dry particles is proposed and its structural characteristics are described. Then, the transmission system and blade parameters of the mixer are designed and calculated, and the blade parameters of the mixers are optimized based on ADAMS and EDEM. Finally, the comparative simulation experiment between planetary gear mixers and SHR-10A mixers is carried out. The experiment is used to inquire on the mixing performance of the new planetary gear mixer. Results: The complementary cycloid was the ideal mixing trajectory of the blade. The most distinctive feature of this motion is that the attack angle of the blade can change in all directions. When the blade parameter p = 11, the Lacey index rises the fastest and the mixing degree is the largest, which indicates that the optimal mathematical model of the blade is ‘y2= 22x’. The comparison with SHR-10A mixer showed that spatial distribution of multi-degree of freedom blades in the new planetary gear mixer has strong dispersion effects on particles and better mixing performance. Conclusion: The planetary gear mixer for dry particle materials is a new type of mixer, which is composed of two sets of blades whose attack angle can be changed at any time. Convection and shear mixing dominate its mixing space, which is conducive to its rapid and full mixing, improving the mixing performance. The dry particle planetary gear mixer for dry particle materials has great developmental value and wide engineering application prospect. In this article, various patents have been discussed.
Keywords: mixer